The Association Between Alzheimer's Disease-Related Markers and Physical Activity in Cognitively Normal Older Adults - Pedrini, Steve; Chatterjee, Pratishtha; Nakamura, Akinori; Tegg, Michelle; Hone, Eugene; Rainey-Smith, Stephanie R.; Rowe, Christopher C.; Dore, Vincent; Villemagne, Victor L.; Ames, David; Kaneko, Naoki; Gardener, Sam L.; et al. (Frontiers in Aging Neuroscience, 2022)
Previous studies have indicated that physical activity may be beneficial in reducing risk for Alzheimer’s disease (AD), although the underlying mechanisms are not fully understood. The goal of this study was to evaluate the relationship between habitual physical activity levels and brain amyloid deposition and AD-related blood biomarkers (measured using a novel high-performance mass spectrometry-based assay), in APOE ε4 carriers and non-carriers. We evaluated 143 cognitively normal older adults, all of whom had brain amyloid deposition assessed using positron emission tomography and had their physical activity levels measured using the International Physical Activity Questionnaire (IPAQ). We observed an inverse correlation between brain amyloidosis and plasma Aβ1-42 but found no association between brain amyloid and plasma Aβ1-40 and APP669-711. Additionally, higher levels of physical activity were associated with lower plasma Aβ1-40, Aβ1-42 and APP669-711 levels in APOE ε4 non-carriers. The ratios of Aβ1-40/Aβ1-42 and APP669-711/Aβ1-42, which have been associated with higher brain amyloidosis in previous studies, differed between APOE ε4 carriers and non-carriers. Taken together, these data indicate a complex relationship between physical activity and brain amyloid deposition and potential blood-based AD biomarkers in cognitively normal older adults. In addition, the role of APOE ε4 is still unclear and more studies are necessary to bring further clarification.